PENGARUH PEMAHAMAN PERPAJAKAN, PENERAPAN SISTEM E-FILING DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Mutiara, Ilva; Efriyenti, Dian (SCIENTIA JOURNAL, 2024)
Indonesia is a developing country that has abundant resources and has useful potential to become a more advanced country. The aim of this research is to test and instill the influence of understanding taxation, implementation of the e-filing system and tax awareness on taxpayer compliance at KPP Pratama South Batam. The data analysis method used is a quantitative method. The number of taxpayers who reported e- filing at KPP Pratama South Batam was 75,569 people, which is the population of individual taxpayers in this study. The sampling procedure was carried out using the Slovin formula calculation. From the Slovin formula calculation, a sample of 398 taxpayers was obtained for this research, individual taxpayers registered at KPP Pratama South Batam. The software used to process this research data uses SPSS version 26. The research results show that Tax Understanding has a significant effect on Taxpayer Compliance, partially the implementation of the e-filing system has a significant effect on taxpayer compliance, tax awareness has a significant effect on taxpayer compliance, and Tax awareness has a significant effect on taxpayer compliance. have a significant effect on the fulfillment of taxpayers and simultaneously understanding taxation, implementation of the e-filing system and tax awareness have an influence on the fulfillment of individual taxpayers at KPP Pratama South Batam